'Rural' rhetoric in 1930s unemployment relief schemes. Issue 1 (29th March 2019) - O'Donnell, Ronan; Petts, David
Abstract: This article examines the role of particular ideas of the countryside in unemployment relief schemes. While interwar thinking on the countryside has received attention, it has not been examined in the specific context of unemployment relief. This article uses four case studies from North East England, namely the Team Valley Trading Estate (Gateshead), Hamsterley Forest Instructional Centre (Durham), Swarland model village (Northumberland) and Heartbreak Hill (Cleveland). All four projects took different approaches to the unemployment problem, but all used some form of rural rhetoric. The ways in which the projects deployed images of the countryside creatively recombined a wide range of ideas to suit their needs rather than being rigidly confined by particular schools of thought.